The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/en12030344
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of Building Renovation Measures–Trade-off between Building Materials and Energy

Abstract: The scope of this study is to assess how different energy efficient renovation strategies affect the environmental impacts of a multi-family house in a Nordic climate within district heating systems. The European Union has set ambitious targets to reduce energy use and greenhouse gas emissions by the year 2030. There is special attention on reducing the life cycle emissions in the buildings sector. However, the focus has often been on new buildings, although existing buildings represent great potential within … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 28 publications
0
32
0
Order By: Relevance
“…Energy performance of building directive (EPBD) [3] requires all new buildings to be nearly Zero Energy Buildings (nZEB) as of the year 2020 and to renovate almost all buildings by the year 2050. Due to the reduction of energy use during the lifetime of buildings, renovation resulted in a reduction of global warming potential [4]. Case studies have shown the viability of the nZEB renovation measures to improve the condition of residential building stock in Croatia [5], Spain [6,7], Poland [8], and the Mediterranean climate [9].…”
Section: Introductionmentioning
confidence: 99%
“…Energy performance of building directive (EPBD) [3] requires all new buildings to be nearly Zero Energy Buildings (nZEB) as of the year 2020 and to renovate almost all buildings by the year 2050. Due to the reduction of energy use during the lifetime of buildings, renovation resulted in a reduction of global warming potential [4]. Case studies have shown the viability of the nZEB renovation measures to improve the condition of residential building stock in Croatia [5], Spain [6,7], Poland [8], and the Mediterranean climate [9].…”
Section: Introductionmentioning
confidence: 99%
“…For this building, eight renovation scenarios were assessed (already defined in [19]). Different combinations of renovation measures were assessed, such as added insulation, energy efficient windows, and heat recovery ventilation (HRV).…”
Section: Case Study Buildingmentioning
confidence: 99%
“…The proposed measures have previously been studied by Ramirez-Villegas et al [19], who consider the electricity mix in Sweden, whereas in this study the electricity mix for different countries has been considered. In Table 2 all used material data is compiled.…”
Section: Life Cycle Inventorymentioning
confidence: 99%
“…The PV production was estimated using PVGIS [18]. More details of the energy simulation can be found in [17,19]. In this study, the energy demand is that stated in the Swedish building code [20] regarding space heating, domestic hot water and facility electricity.…”
Section: Energy Simulationmentioning
confidence: 99%
“…The proposed measures to improve the building envelope have previously been studied in Ramírez-Villegas et al [19]. In this study, photovoltaic panels and a geothermal heat pump were added to the renovation scenarios as these are considered to be cost-effective measures in Sweden [21].…”
Section: Life Cycle Inventorymentioning
confidence: 99%